Penyelesaian Sengketa Mawah Hewan Ternak dalam Masyarakat Kecamatan Pasie Raja menurut Perspektif Hukum Perdata - Salmawati Salmawati; Nouvan Moulia (Prodi Ilmu Hukum, Universitas Teuku Umar, 2022)
Mawah is an agreement made between the owner of the property and the manager in which the proceeds will be divided based on the agreed agreement. Each agreement can be verbal or written, as long as the conditions for the validity of the agreement as stipulated in Article 1320 of the Civil Code are fulfilled. Generally, mawah agreements are made in the agricultural, land, plantation, animal husbandry sectors, and so on. This research aims to examine how the profit sharing agreement of mawah for livestock between farmers and livestock owners in Pasie Raja District, Aceh Selatan Regency, how to resolve profit sharing disputes in the practice of mawah on livestock and how the perspective of civil law on dispute resolution related to profit sharing. The method used in this research is empirical juridical. Collecting data in the field through interviews with respondents and informants, as well as documentation of activities in the field. The results of the study show that the agreement on the practice of mawah for livestock is still carried out orally. In the implementation of the mawah profit sharing agreement, there are differences between male buffalo, female buffalo that have never given birth, and female buffalo that have given birth. Efforts to resolve profit-sharing disputes in the practice of mawah on livestock are by way of deliberation or kinship, and the perspective of civil law regarding dispute resolution related to mawah profit sharing is appropriate, because the settlement route taken is non-litigation.